2023
DOI: 10.3389/fonc.2023.1040673
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after online adaptive MR-guided stereotactic body radiotherapy for pancreatic tumors on a 1.5 T MR-linac

Hidde Eijkelenkamp,
Guus Grimbergen,
Lois A. Daamen
et al.

Abstract: IntroductionOnline adaptive magnetic resonance-guided radiotherapy (MRgRT) is a promising treatment modality for pancreatic cancer and is being employed by an increasing number of centers worldwide. However, clinical outcomes have only been reported on a small scale, often from single institutes and in the context of clinical trials, in which strict patient selection might limit generalizability of outcomes. This study presents clinical outcomes of a large, international cohort of patients with (peri)pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Early studies on patient-reported outcomes indicate a stable quality of life after MR-guided SBRT. 18,159,162 This last point brings us to the role that CBCT-guided radiotherapy might still play in future treatment of pancreatic cancer, which might not be confined to MR-guided systems after all. Cone-beam guided adaptive radiotherapy has only just begun to emerge, 168,169 and clinicians may be hesitant to the prescribe the ablative dose levels on these systems.…”
Section: The Clinical Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Early studies on patient-reported outcomes indicate a stable quality of life after MR-guided SBRT. 18,159,162 This last point brings us to the role that CBCT-guided radiotherapy might still play in future treatment of pancreatic cancer, which might not be confined to MR-guided systems after all. Cone-beam guided adaptive radiotherapy has only just begun to emerge, 168,169 and clinicians may be hesitant to the prescribe the ablative dose levels on these systems.…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…Early results from large cohorts demonstrate that MR-guided SBRT for pancreatic cancer can safely be delivered in high dose regimens, with low acute toxicity rates and no loss of quality of life. [15][16][17][18][19] However, now that MR-guided radiotherapy has been established as a feasible and safe therapy, it has become clear that there are several technical hurdles with regards to treatment planning and delivery that will play increasingly dominant roles as dose is further escalated and PTV margins reduced. 20,21 This section will further outline these limitations and challenges, and set the scene for the work presented in this thesis.…”
Section: Mr-guided Radiotherapy For Pancreatic Cancer: Technical Bene...mentioning
confidence: 99%
See 2 more Smart Citations